Reducing Disability through Early Detection: A Systematic Review of Screening Programs in Saudi Arabia - AL Otaibi Bander Saqer,; AL Omari Fahad Abdulaziz,; AL Mutairi Abdullah Omar,; AL Hariqi Ibrahim Ali,; AL Enazy Hammad Aleyt,; AL Mutairi Agaab Sager,; Bin Shehail Fahad Mohammed,; AL Mutairi Abdullah Rafi,; AL Solami Khalid Aqall, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Early screening programs play a crucial role in identifying potential health risks before they evolve into disabling conditions. In Saudi Arabia, the prevalence of disability has increased due to various chronic diseases and congenital conditions. Objective: This systematic review aims to evaluate the effectiveness, challenges, and implementation strategies of early screening programs in reducing disability in Saudi Arabia. Methods: A comprehensive search of databases such as PubMed, Scopus, and Saudi Digital Library was conducted for articles published between 2016 and 2024. Studies were selected based on inclusion criteria focusing on early detection, disability prevention, and programs implemented within the Saudi healthcare system. Results: The findings revealed significant improvements in health outcomes, especially in programs targeting neonatal screening, vision and hearing impairments, and chronic disease management. Key challenges included low public awareness, limited accessibility in rural areas, and inconsistent follow-up care. Conclusion: Early screening initiatives in Saudi Arabia have demonstrated a promising impact in reducing disability. However, broader policy integration, public education, and infrastructure investment are critical for long-term success.